A novel thermal model for PV panels with back surface spray cooling. (15th September 2022) - Bevilacqua, Piero; Bruno, Roberto; Rollo, Antonino; Ferraro, Vittorio
Abstract: To improve the performances of photovoltaic panels, water-based cooling systems have been considered as an interesting solution. This study proposes a novel mono-dimensional thermal model that includes the spray cooling phenomena on the back surface. The model is based on the energy balance method with a Finite Difference approach providing the thermal field across the thickness, and was validated with data of an experimental setup with a PV panel equipped with two spray nozzles. Simulations were carried out over a large number of days in the summer period with a short time step (5 s). Results showed an average RMSE of 1.37 °C, RMSEP of 0.005% and NSE of 96.5% for the back surface temperature, and an average RMSE of 3.39 W, RMSEP of 0.36% and NSE of 99.6% for the electric power. A further assessment of the cooling phenomenon highlighted the contribution of sensible and latent energy exchanges to the panel energy balance. Finally, a comparison of the performances with a non-cooled PV panel showed an average increase of 7.8% of the electric power in solar radiation peak hours and a reduction of 28.2% of the average cell temperature. Highlights: A novel thermal model including spray cooling for PV panels was proposed. The model was validated with experimental data. An accurate analysis of the cooling phenomena was conducted. The average efficiency in summer increased by 5.4%.